Observing Supernova Neutrino Light Curves with Super-Kamiokande. IV. Development of SPECIAL BLEND: A New Public Analysis Code for Supernova Neutrinos - Akira Harada; Yudai Suwa; Masayuki Harada; Yusuke Koshio; Masamitsu Mori; Fumi Nakanishi; Ken’ichiro Nakazato; Kohsuke Sumiyoshi; Roger A. Wendell (The Astrophysical Journal, 2023)
Supernova neutrinos are invaluable signals that offer information about the interior of supernovae. Because a nearby supernova can occur at any time, preparing for future supernova neutrino observation is an urgent task. For the prompt analysis of supernova neutrinos, we have developed a new analysis code, the “Supernova Parameter Estimation Code based on Insight on Analytic Late-time Burst Light curve at Earth Neutrino Detector” ( SPECIAL BLEND ). This code estimates the parameters of supernovae based on an analytic model of supernova neutrinos from the proto-neutron star cooling phase. For easy availability to the community, this code is public and easily runs in web environments. SPECIAL BLEND can estimate the parameters better than the analysis pipeline we developed in a previous paper. By using SPECIAL BLEND , we can estimate the supernova parameters within 10% precision up to ∼20 and ∼60 kpc (Large Magellanic Cloud contained) with Super-Kamiokande and Hyper-Kamiokande, respectively.